Transformasi Tata Kelola Publik melalui Governansi Digital pada Layanan Administrasi Kependudukan di Kabupaten Gowa - Anisa Fitri fitri; Widyawati; Nina Agustina; Putri Dzakilla Handayani; Nurkumalasari Syam (Jurnal Ilmiah Administrasita', 2026)
This study aims to analyze the transformation of public governance through the implementation of digital governance in population administration services at the Department of Population and Civil Registration of Gowa Regency. The development of information and communication technology has encouraged local governments to provide digital-based public services that are more effective, transparent, and accessible. However, the implementation of digital governance in regions that are still undergoing digital transition faces various challenges, particularly related to community digital literacy and service accessibility. This study employed a qualitative approach with a descriptive research design. Data were collected through observation, interviews, and documentation at the Department of Population and Civil Registration of Gowa Regency. The analysis referred to the Digital Government Transformation theory proposed by Janowski (2015), which consists of the dimensions of digitization, transformation, engagement, and contextualization. The findings indicate that the implementation of digital governance has transformed population administration services from a manual system into digital-based services through the use of WhatsApp, Google Forms and Spreadsheets, and eventually an integrated website-based service system. The implementation has improved service efficiency, accelerated administrative processes, reduced service queues, and expanded public access to services, particularly for communities in rural and remote areas. In addition, digital governance has encouraged changes in bureaucratic work patterns to become more systematic, transparent, and data-driven. Nevertheless, this study found that the implementation of digital governance still faces challenges related to community digital literacy, service system optimization, internet accessibility, and the adaptability of services to local community capacities. This study concludes that the success of digital governance is determined not only by technological readiness but also by the government’s ability to adapt public services to the social, geographical, and contextual needs of local communities.